Design and ex-ante analysis for technological interventions - Pezo, Danilo A. (International Livestock Research Institute, 2000)
The design of technological interventions and their ex ante evaluation is one of the most critical steps in farming systems research, since it is an initial effort to find solutions to those problems prioritised by farmers. This paper discusses the design of technological interventions with reference to criteria for designing technological interventions, and elements required for the description of technological options. It highlights ex-ante assessment of technological interventions with regard to estimation of potential biological responses; use of quantitative formats; and use of simulation models. This paper also examines the different procedures for estimating the economic feasibility of technological interventions in a system, which include partial budget techniques, gross-margin analysis, cost-benefit analysis; sensitivity analysis, cash flow analysis, and labour profile analysis. Farmer's participation in ex-ante evaluation of technological interventions, and techniques for ranking and scoring alternatives are also outlined in this paper.